Mobilidade urbana: proposições sobre a implantação das 13 passarelas de estruturas metálicas na BR 316 - SANTA ROSA, Bernardo Augusto Campina (2024)
The Metropolitan Region of Belém, over the years, has gone through the process of urban development in the cities that compose it. The main access road to the region is the BR-316 highway, which needs to serve a high flow of people and vehicles from various segments. However, the infrastructure of the transport system, especially the walkways for pedestrian and cyclist crossings, needs a major readjustment to meet the new needs. Thus, in 2019, work began on the implementation of the BRT (Bus Rapid Transit) on the first stretch of BR-316, from Km 1 to Km 10. The present work proposes to analyze and generate two hypotheses about the implementation of the new footbridges and their relevant changes in road safety and pedestrian accessibility. A 51.17% reduction in the average distance between walkways was observed and evidence was presented that walkways will promote greater comfort for pedestrians. The data was calculated in the Power BI software and presented in map format. The design documentation of the project of the walkways, from the National Department of Transport Infrastructure (DNIT) and NBR 9050 (Accessibility to buildings, equipament and the urban environment) was used as a reference.